The First Mitochondrial Genome of Ciborinia camelliae and Its Position in the Sclerotiniaceae Family - Valenti, Irene; Degradi, Luca; Kunova, Andrea; Cortesi, Paolo; Pasquali, Matias; Saracchi, Marco (Frontiers in Fungal Biology, 2022)
Ciborinia camelliae is the causal agent of camellia flower blight (CFB). It is a hemibiotrophic pathogen, inoperculate Discomycete of the family Sclerotiniaceae. It shows host and organ specificity infecting only flowers of species belonging to the genus Camellia, causing serious damage to the ornamental component of the plant. In this work, the first mitochondrial genome of Ciborinia camellia is reported. The mitogenome was obtained by combining Illumina short read and Nanopore long read technology. To resolve repetitive elements, specific primers were designed and used for Sanger sequencing. The manually curated mitochondrial DNA (mtDNA) of the Italian strain DSM 112729, is a circular sequence of 114,660 bp, with 29.6% of GC content. It contains two ribosomal RNA genes, 33 transfer RNAs, one RNase P gene, and 62 protein-coding genes. The latter include one gene coding for a ribosomal protein (rps3) and the 14 typical proteins involved in the oxidative metabolism. Moreover, a partial mtDNA assembled from a contig list was obtained from the deposited genome assembly of a New Zealand strain of C. camelliae. The present study contributes to understanding the mitogenome arrangement and the evolution of this phytopathogenic fungus in comparison to other Sclerotiniaceae species and confirms the usefulness of mitochondrial analysis to define phylogenetic positioning of this newly sequenced species.